# Factoring the Difference of Squares

How to factor the difference of squares: formula, examples, and their solutions.

## Formula

Recall (*a* + *b*)(*a* - *b*) formula.

If you switch both sides,

you get this factoring formula:*a*^{2} - *b*^{2} = (*a* + *b*)(*a* - *b*).

## Example 1

*x*^{2} - 25 = *x*^{2} - 5^{2}

Use *x* and 5 to factor it.

## Example 2

16*a*^{2} - 49*b*^{2} = (4*a*)^{2} - (7*b*)^{2}

Use 4*a* and 7*b* to factor it.

## Example 3

*k*^{4} - 1 = (*k*^{2})^{2} - 1^{2}

Use *k*^{2} and 1 to factor it.

*k*^{2} - 1 = *k*^{2} - 1^{2}

Use *k* and 1 to factor it again.